"With Widened Hearts": A Commentary on the Prologue of the Rule of Suint Benedict - Day, Agnes (Cistercian studies quarterly, 2016)
In this article, author comments on prologues from the book "Rules of Saint Benedict." Topics discussed include differentiation of listening and hearing, instructions to love God and believe in God by listening to conscience and suggestions to deal with different situations of life by understanding importance of obedience and loving kindness.